2015
DOI: 10.1099/ijs.0.055160-0
|View full text |Cite
|
Sign up to set email alerts
|

Allosalinactinospora lopnorensis gen. nov., sp. nov., a new member of the family Nocardiopsaceae isolated from soil

Abstract: A novel actinomycete, designated strain CA15-2 T , was isolated from a soil sample collected from the rhizosphere of tamarisk in the Lop Nor region, Xinjiang, China, and was characterized by using a polyphasic taxonomic approach. Optimal growth occurred at 37 6C and pH 7.5-8.0 and with 5 % (w/v) NaCl. Strain CA15-2 T formed white to pale-yellow branched substrate mycelium without fragmentation and sparse aerial mycelium with wavelike curves. Whole-cell hydrolysates of the isolate contained meso-diaminopimelic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…[14], separated and then determined by HPLC coupled with a single quadrupole mass spectrometer as described by Guo et al . [15]. Diagnostic isomers of DAP and sugar compositions in whole cell hydrolysates were prepared and determined by TLC on aluminum cellulose sheets (Merck) as described by Staneck and Roberts [16] and Hasegawa et al .…”
Section: Full-textmentioning
confidence: 99%
“…[14], separated and then determined by HPLC coupled with a single quadrupole mass spectrometer as described by Guo et al . [15]. Diagnostic isomers of DAP and sugar compositions in whole cell hydrolysates were prepared and determined by TLC on aluminum cellulose sheets (Merck) as described by Staneck and Roberts [16] and Hasegawa et al .…”
Section: Full-textmentioning
confidence: 99%
“…), respectively. Menaquinones were extracted using the method of Collins et al (1977), and then analysed and confirmed by HPLC and a single quadrupole mass spectrometer LCMS-2020 (Shimadzu) as described by Guo et al (2015).…”
Section: Cells Of Strain J11y309mentioning
confidence: 99%
“…Analyses of polar lipids and menaquinones were performed by cultivating strains in tryptic soy broth (TSB) medium (pH 7-8) at 28 °C for 3 days in an orbital shaker. Menaquinones were purified following the previously described method [32] and analysed by HPLC/MS [33]. The polar lipids were extracted according to the method described by Minnikin et al [34] using twodimensional thin-layer chromatography (TLC) on silica gel 60 F254 plates (Merck).…”
mentioning
confidence: 99%